Growth and yield of anthurium in response to gibberellic acid - Juliana Domingues Lima; Nathalia Felipe Ansante; Edson Shigueaki Nomura; Eduardo Jun Fuzitani; Silvia Helena Modenese-Gorla da Silva (Ciência Rural, 2014)
Gibberellic acid (GA3) induces flowering of plants of various genera of the Araceae family. Therefore, it was evaluated the effect of GA3 on the growth and yield of Anthurium andraeanum cv. 'Apalai'. For this purpose, micropropagated seedlings were planted in nursery beds under 70% shade. The experimental design was completely randomized in subdivided plots with eight replications. The growth regulation effect was assessed in each plot and the time to flowering after the start of the treatments was assessed in each subplot. The GA3 concentrations were 0, 150, 300, 450 and 600mg L-1, applied every 60 days by spraying on the leaves. The applications and evaluations started after the production of marketable floral stems. Every month the number of leaves was counted and their dimensions were measured, while every week the presence of inflorescences and the point of their commercial harvest were assessed and the respective dimensions were measured. Application of GA3 at 150, 300 and 450 mg L-1 promoted an increase in the leaf area. However, there was no increase in the number of inflorescences produced or their quality, making it impossible to recommend the use of this growth regulator for commercial production of this flower.